Inhibition of SARS-CoV-2 in Vero cell cultures by peptide-conjugated morpholino oligomers. (9th November 2020) - Rosenke, Kyle; Leventhal, Shanna; Moulton, Hong M; Hatlevig, Susan; Hawman, David; Feldmann, Heinz; Stein, David A
Abstract: Background: As the causative agent of COVID-19, SARS-CoV-2 is a pathogen of immense importance to global public health. Development of innovative direct-acting antiviral agents is sorely needed to address this virus. Peptide-conjugated morpholino oligomers (PPMO) are antisense compounds composed of a phosphorodiamidate morpholino oligomer covalently conjugated to a cell-penetrating peptide. PPMO require no delivery assistance to enter cells and are able to reduce expression of targeted RNA through sequence-specific steric blocking. Methods: Five PPMO designed against sequences of genomic RNA in the SARS-CoV-2 5′-untranslated region and a negative control PPMO of random sequence were synthesized. Each PPMO was evaluated for its effect on the viability of uninfected cells and its inhibitory effect on the replication of SARS-CoV-2 in Vero-E6 cell cultures. Cell viability was evaluated with an ATP-based method using a 48 h PPMO treatment time. Viral growth was measured with quantitative RT–PCR and TCID50 infectivity assays from experiments where cells received a 5 h PPMO treatment time. Results: PPMO designed to base-pair with sequence in the 5′ terminal region or the leader transcription regulatory sequence region of SARS-CoV-2 genomic RNA were highly efficacious, reducing viral titres by up to 4–6 log10 in cell cultures at 48–72 h post-infection, in a non-toxic and dose-responsive manner. Conclusions: The data indicate that PPMO have the ability to potently and specifically suppress SARS-CoV-2 growth and are promising candidates for further preclinical development.